Q. 45.0( 1 Vote )

# If the equation (4a – 3) x2 + ay2 + 6x – 2y + 2 = 0 represents a circle, then its centre isA. (3, - 1)B. (3,1)C. (- 3,1)D. none of these

Given that the equation of the circle is:

(4a - 3)x2 + ay2 + 6x - 2y + 2 = 0 ..... (1)

Comparing with the standard equation of circle:

x2 + y2 + 2ax + 2by + c = 0

We get

4a - 3 = a

4a - a = 3

a = 1

Substituting a value in (1), we get

(4(1) - 3)x2 + 1y2 + 6x - 2y + 2 = 0

x2 + y2 + 6x - 2y + 2 = 0

We know that for a circle x2 + y2 + 2ax + 2by + c = 0

Centre = (- a, - b)

Centre(C) =

The correct option is (c)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Lecture on Common tangents & angle of intersection of 2 circles56 mins
Lecture on radical axis of 2 circles48 mins
Lecture on Tangents to a Circle57 mins
General & parametric form of circle56 mins
Practice Problems on Equation of Circle54 mins
Family of circles55 mins
Locus involving circles45 mins
Interactive quiz on equation of circle50 mins
Interactive Quiz on Family of circles58 mins
Quiz on Tangents to a Circle48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses